The impact of firm’s capabilities on digital brand performance of SME’s online business - Masran Tamin; Azaze Azizi Abdul Adis (Penerbit UMS, 2019)
In online business, firms are very sensitive to any changes in the market including internet application for business operation usage. The growth of online business in Malaysia is not in line with the interest of digital brand performance to improve the competitiveness of the companies and maintain their position in the market. Hence, this study aims to investigate the factors that influence digital brand performance in SME. This study employed Resource Based View (RBV) theory which is a unifying framework for the fundamental determinant of digital brand performance. The study examines the relationship between firm’s capabilities (innovation capability, branding capability, market-sensing capability, human and organization capability) and digital brand performance. A total of 155 SMEs online business participated in this study. The result of this study found that both market sensing and human and organization capability have significant impact on digital brand performance in SMEs context. Recommendation and suggestion for future research were also discussed to improve digital brand performance for Malaysian SMEs online business.